Mesoscopic Finite Element modelling of non-crimp fabrics for drape and failure analyses - Creech, G. (Cranfield University, 2006)
To date, macroscopic analysis methods have been invariably used to analyse textile composite structures for forming and mechanical performance. Techniques such as geometric ‘mapping’ for the draping of textile fabrics and classical laminate analysis combined with simplified failure criteria to determine mechanical performance have formed the basis of most of these methods. The limited accuracy of the physical laws applied is appropriate to macro- analysis methods in which the fibre-matrix composite is treated as homogeneous medium. Today, however, modern high performance computers are opening new possibilities for composites analysis in which far greater detail of the composite constituent materials may be made. This paper presents Finite Elements techniques for the draping simulation of textile composites, specifically biaxial Non Crimp Fabrics, in which the complex deformation mechanisms of the dry tows and stitching may be properly modelled at the individual tow and stitch mesoscopic level. The resulting ‘deformed’ Finite Element model is then used to provide a basis for accurate simulation of the impregnated composite structure. The modelling techniques for both draping and structural analysis are presented, together with validation results for the study of a relatively large scale hemisphere composite part.